PENGEMBANGAN MODEL BIMBINGAN KARIR SISWA KELAS 1 SMA KOTA MADYA MEDAN DI ERA REVOLUSI INDUSTRI 4.0 - Edidon Hutasuhut; Mirza Irawan; Utami Nurhafsari Putri (Universitas Negeri Medan, 2020)
This study aims to obtain teaching materials or career guidance materials that will be used in school. After conducting the research, it was found that 32 career guidance materials had been provided by BK teachers in SMA Negeri Medan. From this material, research was carried out on 30 alumni of Medan City Public High School. The results show that out of 32 materials, there are 6 materials that are unnecessary. Meanwhile, based on the opinion of 3 BK experts from the 6 materials, it can be used as a material entitled